Upper Gastrointestinal Symptoms Predictive of Candida Esophagitis and Erosive Esophagitis in HIV and Non-HIV Patients: An Endoscopy-Based Cross-Sectional Study of 6011 Patients. Issue 47 (November 2015) - Takahashi, Yuta; Nagata, Naoyoshi; Shimbo, Takuro; Nishijima, Takeshi; Watanabe, Koji; Aoki, Tomonori; Sekine, Katsunori; Okubo, Hidetaka; Watanabe, Kazuhiro; Sakurai, Toshiyuki; Yokoi, Chizu; Mimori, Akio; et al.
Abstract : Abstract: Upper gastrointestinal (GI) symptoms are common in both HIV and non-HIV-infected patients, but the difference of GI symptom severity between 2 groups remains unknown. Candida esophagitis and erosive esophagitis, 2 major types of esophagitis, are seen in both HIV and non-HIV-infected patients, but differences in GI symptoms that are predictive of esophagitis between 2 groups remain unknown. We aimed to determine whether GI symptoms differ between HIV-infected and non-HIV-infected patients, and identify specific symptoms of candida esophagitis and erosive esophagitis between 2 groups. We prospectively enrolled 6011 patients (HIV, 430; non-HIV, 5581) who underwent endoscopy and completed questionnaires. Nine upper GI symptoms (epigastric pain, heartburn, acid regurgitation, hunger cramps, nausea, early satiety, belching, dysphagia, and odynophagia) were evaluated using a 7-point Likert scale. Associations between esophagitis and symptoms were analyzed by the multivariate logistic regression model adjusted for age, sex, and proton pump inhibitors. Endoscopy revealed GI-organic diseases in 33.4% (2010/6.011) of patients. The prevalence of candida esophagitis and erosive esophagitis was 11.2% and 12.1% in HIV-infected patients, respectively, whereas it was 2.9% and 10.7 % in non-HIV-infected patients, respectively. After excluding GI-organic diseases, HIV-infected patients had significantly ( P  < 0.05) higher symptom scores for heartburn, hunger cramps, nausea, early satiety, belching, dysphagia, and odynophagia than non-HIV-infected patients. In HIV-infected patients, any symptom was not significantly associated with CD4 cell count. In multivariate analysis, none of the 9 GI symptoms were associated with candida esophagitis in HIV-infected patients, whereas dysphagia and odynophagia were independently ( P  < 0.05) associated with candida esophagitis in non-HIV-infected patients. However, heartburn and acid regurgitation were independently ( P  < 0.05) associated with erosive esophagitis in both patient groups. The internal consistency test using Cronbach's α revealed that the 9 symptom scores were reliable in both HIV (α, 0.86) and non-HIV-infected patients (α, 0.85). This large-scale endoscopy-based study showed that HIV-infected patients have greater GI symptom scores compared with non-HIV-infected patients even after excluding GI-organic diseases. None of the upper GI symptoms predict candida esophagitis in HIV-infected patients, but dysphagia and odynophagia predict candida esophagitis in non-HIV-infected patients. Heartburn and acid regurgitation predict erosive esophagitis in both patient groups.